Proposing a model to predict students perception towards adopting an e-assessment system - Farzin, Shervin (JATIT, 2016)
Information communication technology (ICT) is the buzzword of the 21st century. The letter ‘E’ appear s in the words e-commerce, e-learning, e-banking and etc. In essence, the said letter reflects the ICT component that is utilized in providing more ‘reach ’ in addition to making more effective and efficient commercial transactions, information and knowledge transactions and financial transactions to name a few. An e-based system will be utilized when there are supportive factors that collectively encourage its use. The perspective of the user is an undeniably import ant component. E-based systems may exist in an educational environment for varied purposes. Assessments inevitably play a role in such an educational environment as one of the many ways available to measure students learning outcomes. Thus, this study was conducted to explore students’ perspective on engaging in an e-assessment experience. In that sen se, the first and foremost step forward would be to recognize and identify real world problems and issued students are facing in their practice. So as to reach this goal, the study moved forward with the phase of article selection which is done through well-known academic databases. In continue, selected articles went through filtering phase so the most relevant studies disclosed. Secondly, to map those identified issues with corresponding behavioral factors of adoption. As a result, this could set the stage right for future s tudies on resolving issues and enhancing the e-assessment practice. This study reveals that UTAUT is the most suited underlying theory, and two constructs, namely Computer Anxiety and Habit are incorporated into the model to tailor the UTAUT so it could fit the case of e-assessment adoption.